Detection of Neospora caninum antibodies in beef cattle in Tamaulipas, Mexico. Case report - Rábago-Castro, Jaime Luis; Jasso-Obregón, José Osiel; Zertuche-Rodríguez, Jorge Luis; Sánchez-Martínez, Jesús Genaro; Loredo-Osti, Jorge; Domínguez-Muñoz, Miguel Ángel (Austral Journal of Veterinary Sciences, 2017)
The objective of this study was to determine whether Neospora caninum is prevalent in beef cattle in Tamaulipas (Mexico), using a commercial enzyme-linked immunosorbent assay (ELISA) kit in 182 serum samples from six municipalities with different climates. The overall seroprevalence was 11.9% in animals and 78.6% in herds.